Trajectories and experiences of schooling of women in situations of imprisonment - Maria Celeste Reis Fernandes Souza; Maria Gabriela Parenti Bicalho; Eunice Maria Nazarethe Nonato (Arizona State University, 2013)
This article is part of the discussion on the Education of women in situations of deprivation of liberty, a topic that has received attention from scholars in the field of Young and Adult Education. The data presented were collected in the context of a study that analyzed how the educational experiences of educated women are shaped in situations of imprisonment in the State of Minas Gerais. It refers specifically to reports produced on interviews with 5 women who attend school in one of these institutions, and 1 educator who is responsible for monitoring educational experiences in state prisons. The analysis of the interviews uses the theory of relationship with knowledge proposed by Bernard Charlot, especially the concepts of mobilization, sense and activity. The reports of school experiences show two different situations with regard to the conditions of access to basic education and the retention of students to it: paths marked by difficulties and halted prematurely, and other more regular and long lasting trajectories. Therefore prison is for some women the possibility of resuming elementary school, and for others, the inability to get to secondary school. Despite these differences, it is possible to identify common aspects in the stories that range from the perspectives on school education to the mobilization in relation to learning and achievement in school activities in prison. These aspects are presented and discussed as essentially important elements in order to understand the complex reality of the education of young and adult females in the prison system.